Diversity, Equity, and Inclusion in Otolaryngology–Head and Neck Surgery: The Big Picture. (29th January 2023) - Haugen, Thorsen; Pai, Kavya; Desiato, Vincent; Lesh, Randy
Abstract: Efforts are being made to achieve equitable health care for all, in addition to providing equal opportunity for those working within the health care system. Many challenges, however, still need to be overcome as research increasingly brings to light new areas of concern. In this commentary, we highlight recently published findings within the field of otolaryngology in the United States. These findings are then discussed within the context of global health care disparities to emphasize the importance of equitable health care on a global scale.